Perception of Marketing Mix on Consumer Satisfaction and The Relations with Intention to Revisit in Mangsi Coffee - OVITA, NI WAYAN VIVI; SURYAWARDANI, I G A OKA; AGUNG, I DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Perception of Marketing Mix on Consumer Satisfaction and The Relations with Intention to Revisit in Mangsi Coffee Mangsi Coffee is one coffee shop in Denpasar area, as one of the tourism facilities in Bali. Rapid market competition resulted in Mangsi needing to pay attention to customer satisfaction. Consumer satisfaction is measured through consumer perceptions by assessing the marketing strategies that have been applied. The purpose of this study is to identify indicators forming marketing mix variables that affect customer satisfaction and its relationship with intention to revisit in Mangsi Coffee. This research was conducted at Mangsi Coffee Sanur and Merdeka with 100 respondents. The analysis used is Structural Equation Model (SEM). The results showed that the product variable was formed by 5 brand indicators, taste, presentation, aroma, and product variation. Price variables are formed by 3 indicators, namely affordability, price suitability, and price competitiveness. Promotion variables are formed by 4 indicators of service, media, quality, and quantity of promotion. Place variables are formed by 4 indicators of comfort, decoration, cleanliness and service. The results of the direct influence of exogenous variables on endogenous variables with a significant level is 5% (0.05) indicate that all direct relationships have a significant and positive effect. The influence of the most significant marketing mix variables on customer satisfaction is the promotion variable is 21.7% (0.217) with p-Value is 0.065. The effect of variable customer satisfaction on intention to revisit is 77.3% (0.773) with a p-Value is 0.000. The results showed that consumer satisfaction at Mangsi Coffee was good but an evaluation of marketing strategy was needed if a marketing strategy was changed.